Gabapentin-induced coma in a patient with renal failure - Dogukan, Ayhan; Aygen, Bilge; Berilgen, Muhammed S.; Dag, Sait; Bektas, Sevim; Gunal, Ali I. (My University, 2006)
We describe a 60-year-old woman who became comatose after a single dose of gabapentin for right-sided sciatalgia. The patient was improved by hemodialysis. Gabapentin toxicity should be considered when mental status changes develop in patients with renal failure after even a single dose. © 2006 International Society for Hemodialysis.
Keywords: Coma; Gabapentin; Renal failure